A Review of Educational Adaptation During the COVID-19 Pandemic via Online Learning - Siripipatthanakul, Supaprawat; Kaewpuang, Pichart; Sitthipon, Tamonwan; Sriboonruang, Patcharavadee (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – This study explains how the educational sector adapts to become more effective in the long run regarding the COVID-19 pandemic has caused significant hardship for families, children, educators, and teachers. Learning has been adapting to the digital economy.   Method – The researchers employed the documentary method in this review article. Random sampling from reliable and valid sources was utilised in the first step and was analysed using content analysis from the selected papers adopting purposive sampling in the second step. Results – The findings reveal that in most countries, the COVID-19 lockdowns have produced a blended learning model that combines face-to-face education with e-learning. This means that class sizes have been reduced, students and teachers must maintain social distance, and learning schedules are staggered. Moreover, students can continue their education using online resources such as language apps, video conferencing tools, and virtual tutoring. Conclusion – Teachers have had to adapt to the educational world in distance education. Most teachers in schools and universities face this challenge, even though teachers lack the skills and equipment to provide adequate distance education in many developing nations. As governments consider reopening schools following the easing of quarantine restrictions, the safety of students and teachers should take precedence, and social isolation of students, access to personal protective equipment, and routine virus testing will be crucial. Recommendations –The role of instructors must shift from knowledge educator to learning motivator and progress manager. Additionally, the investment in the Information and Communication Technology (ICT) infrastructure of the education service to improve educational outcomes should be considered. Research Implications – The internet and technology in the classroom should be given serious consideration to becoming more competent. The government must improve and alter teachers' perceptions of educational technology integration. As teachers play a crucial role in ensuring that any new policy is implemented effectively and efficiently, they are essential in implementing any new initiative.